2021
DOI: 10.1186/s12916-021-01941-6
|View full text |Cite
|
Sign up to set email alerts
|

The trends and associated adverse maternal and perinatal outcomes of labour neuraxial analgesia among vaginal deliveries in China between 2012 and 2019: a real-world observational evidence

Abstract: Background There is a lack of national report of the labour neuraxial analgesia (NA) rates in China in recent years, especially after the national promotion policy. The adverse maternal and perinatal outcomes associated with NA in China are also unknown. The aim of this study is to estimate the trends of NA rates from 2012 to 2019, to evaluate the effect of national policy on promoting NA and to identify the association between NA and adverse outcomes in China. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
1
5
1
1
Order By: Relevance
“…8 We compared this sample with that from China's National Maternal Near Miss Surveillance System (NMNMSS) (Supplemental Digital Content 1, Table 1, http://links.lww.com/AA/E267), which includes over 1.2 million births per year, accounting for 8% of the annual birth number in China. 12 The puerperae characteristics' distribution in CLDS was consistent with that in NMNMSS study (goodness-of-fit test, P > .05), except for the region distribution.…”
Section: Study Design and Study Populationsupporting
confidence: 78%
“…8 We compared this sample with that from China's National Maternal Near Miss Surveillance System (NMNMSS) (Supplemental Digital Content 1, Table 1, http://links.lww.com/AA/E267), which includes over 1.2 million births per year, accounting for 8% of the annual birth number in China. 12 The puerperae characteristics' distribution in CLDS was consistent with that in NMNMSS study (goodness-of-fit test, P > .05), except for the region distribution.…”
Section: Study Design and Study Populationsupporting
confidence: 78%
“…The incidence rate of NLA at the JDWNRH in Bhutan was 3.5%. The incidence was lower than that in the USA, France, China, and Japan [9–12]. Nevertheless, those data are from the developed countries where labor analgesia existed for more than five decades [13].…”
Section: Discussionmentioning
confidence: 99%
“…NLA is common in the USA and Europe [9, 10] compared to the Asian countries [11, 12]. In developing countries, the data on women receiving labor analgesia are limited.…”
Section: Introductionmentioning
confidence: 99%
“…And the two-child policy may result an increased rate cause 90% of women with previous caesarean section eventually gave birth by caesarean section [ 27 ]. Since the National Health Commission issued two policies in 2018 to promote labor neuraxial analgesia in China, the estimated national labor neuraxial analgesia rates increased from 8.4% in 2012 to 16.7% in 2019 [ 8 , 28 , 29 ]. Our results showed that more than half of the surveyed hospitals provide analgesia during labor, with a ratio of 42.3% of parturients receiving analgesia, which is much higher than the value of 16.7% reported in 2019.…”
Section: Discussionmentioning
confidence: 99%